9. EFFECTIVENESS OF PPM INTERVENTION ON TUBERCULOSIS CARE IN PRIVATE SECTOR IN HANOI FROM 2021-2022 (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness of the PPM model on the TB care quality in the private sector, we conducted an interventional study with a control group involving 100 private healthcare facilities in Hanoi.Methods: The interventions included TB training for healthcare workers, test support, assistance with case notification, and financial support. The primary outcome was the number of TB notification and referrals to the National TB Control Program.Results: The results showed that the intervention resulted in significantly more notifications and referrals in the intervention group compared to the control group, with average differences of 36.65 notification/facility/year and 27.59 referrals/facility/year (p < 0.05).Conclusion: These interventions had positive impacts on TB prevention and control, therefore the PPM model should be recommended for nationwide implementation.
Keywords: TB care, tuberculosis, private health facilities, PPM, intervention